2021
DOI: 10.3892/etm.2021.10746
|View full text |Cite
|
Sign up to set email alerts
|

Blocking tumor necrosis factor-α delays progression of chronic obstructive pulmonary disease in rats through inhibiting MAPK signaling pathway and activating SOCS3/TRAF1

Abstract: The present study was conducted in order to study the detailed molecular mechanism of tumor necrosis factor (TNF)-α in chronic obstructive pulmonary disease (COPD). The rats were treated with cigarette smoke (CS) and lipopolysaccharide (LPS) to establish the COPD model. Next, the changes in lung injury in COPD rats with TNF-α knockdown was tested. Meanwhile, the regulation of TNF-α on MAPK pathway and its downstream molecules (SOCS3/TRAF1) was determined by western blotting. On this basis, the activation of MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In addition, accompanied emphysematous changes due to parenchymal destruction with reduced ability for gas exchange and refractory asthma might have a share in the expiratory functional deterioration [ 10 , 47 ]. Previous studies were also in support of our study indicating airflow limitation mainly during the expiration demonstrated the same results showing that the expiratory lung function indices were affected in the COPD group [ 19 , 55 , 79 , 82 ]. However, Xiao et al [ 82 ] showed significant changes in inspiratory parameters as well, but they used different methods of induction and measurement techniques so as they induced COPD using cigarette smoking only for 28 weeks and stated that the inspiratory changes occurred after 14 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, accompanied emphysematous changes due to parenchymal destruction with reduced ability for gas exchange and refractory asthma might have a share in the expiratory functional deterioration [ 10 , 47 ]. Previous studies were also in support of our study indicating airflow limitation mainly during the expiration demonstrated the same results showing that the expiratory lung function indices were affected in the COPD group [ 19 , 55 , 79 , 82 ]. However, Xiao et al [ 82 ] showed significant changes in inspiratory parameters as well, but they used different methods of induction and measurement techniques so as they induced COPD using cigarette smoking only for 28 weeks and stated that the inspiratory changes occurred after 14 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…COPD patients have previously been shown to exhibit elevated pulmonary TNF-α concentrations as compared to healthy individuals, and TNF-α has been linked to COPD progression [51] . Overexpression of TNF-α can lead to emphysema, pulmonary brosis, and muscle mass reduction in COPD patients [52] . Individuals with COPD exhibit characteristic in ammation that affects the airways, pulmonary vasculature, and parenchyma such that higher numbers of T cells and macrophages are present within the lungs.…”
Section: Discussionmentioning
confidence: 99%